(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
Electric distribution systems can present faults that affect the quality of service and create discomfort among users. This type of breakdown generally requires maneuvers that require time to restore. In this sense, the implementation of ADVC-IOEX SCHNEIDER cards was evaluated to restore the power circuits of the Celso Castellanos Electric Substation to their normal service conditions without resorting to complicated manual maneuvers. For this, the current state conditions of each recloser were analyzed, such as: load regime, fault occurrence, alert and communication protection systems, event log, among others; that allow to carry out the programming logic of the equipment and under visual inspection data mechanical and electrical plans were designed, taking into account the environmental conditions of the area, adequacy of space and feasibility of the substation facilities that allow the modification and maintenance of the system implemented, lastly, maneuver tests were carried out with electrical equipment through primary injection tests to verify the output signals required on the Remote Control panel of Feeders. The results found show that the implementation and development of the ADVC-IOEX cards are essential to improve security, reliability, speed, and the support of maneuver for the restoration of the distribution of the electrical circuits of the Celso Castellanos Electric Substation, given that the previous diagnosis of the national electrical system reflects that the failures of the electrical distribution systems are important and affect the performance of economic activities in the agro-industrial sector.